2020
DOI: 10.1002/mp.13570
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for radiation outcome modeling and prediction

Abstract: Aims This review paper intends to summarize the application of machine learning to radiotherapy outcome modeling based on structured and un‐structured radiation oncology datasets. Materials and methods The most appropriate machine learning approaches for structured datasets in terms of accuracy and interpretability are identified. For un‐structured datasets, deep learning algorithms are explored and a critical view of the use of these approaches in radiation oncology is also provided. Conclusions We discuss th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 97 publications
1
17
0
Order By: Relevance
“…This goes in line with the findings from more fundamental ML research studies, which have reported RFs as one of the best classical learning algorithms [133]. However, many other works in the medical field have also compared the accuracy of RFs against more complex or simpler ML classifiers, and it is well known that their performance may vary for different applications [103,113,132,[134][135][136][137][138][139] and even for different datasets within the same application [131,132]. This makes it hard to conclude on the absolute superiority of RFs algorithm over other ML classifiers.…”
Section: Random Forests (Rfs)supporting
confidence: 80%
“…This goes in line with the findings from more fundamental ML research studies, which have reported RFs as one of the best classical learning algorithms [133]. However, many other works in the medical field have also compared the accuracy of RFs against more complex or simpler ML classifiers, and it is well known that their performance may vary for different applications [103,113,132,[134][135][136][137][138][139] and even for different datasets within the same application [131,132]. This makes it hard to conclude on the absolute superiority of RFs algorithm over other ML classifiers.…”
Section: Random Forests (Rfs)supporting
confidence: 80%
“…Therefore, interpretable models are required to establish correlations between quantitative formula-derived radiomics features and genetic subtypes. Representative classification methods include conventional logistic regression ( 45 ) and advanced machine learning techniques ( 46 ), such as decision trees and random forests, support vector machines, and deep neural networks ( 47 ), which are able to emulate human intelligence by acquiring knowledge of the surrounding environment from the input data and detect nonlinear complex patterns in the data.…”
Section: Development Of Radiomics Prediction Modelsmentioning
confidence: 99%
“…However, there was also evidence that the superiority of ML in outcome prediction is not always supported ( Christodoulou et al, 2019 ). In addition, the ML models and algorithms have their own limitations, notably, overfitting ( Zhen et al, 2017 ), and lack of interpretability ( Luo et al, 2019 ; Luo et al, 2020 ). Overfitting would undermine predictive performance.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, artificial intelligence especially machine learning (ML) has a great capacity to process huge and complex data and thus has been used in many areas including medicine. Recently, ML has been introduced into radiation oncology to predict clinical outcomes ( Kang et al, 2015 ; Luo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%